THE MEANING, ORIGIN AND USE OF MASONRY PENDENTIVES AT THE EARLY CHRISTIAN ARCHITECTURE - Marković, Ivica (Arhitektura i urbanizam, 2020)
The construction and function of the masonry pendentives, defined as a triangular section of a sphere, have been extensively examined. However, its genesis and the very conceptual definition continue to raise doubts. Therefore, the main topic of this paper is the origin, development and application of this constructively, acoustically and aesthetically functional element, which is the most commonly used in church architecture for the constructive transition from the circular base of the dome to square body of the building. The paper examines the problem of terminology, noted in our and foreign literature, and gives an overview of constructive assemblies in which this spherical element is included. The paper focuses only on brick and lime mortar pendentives and examines their morphology, method of execution, static properties and structural content. The goal is that through historical analysis, research bring us closer to the answer: how and when did pendentive occurs and what are the main lines of its development? Was it Middle Eastern, Hellenistic or Roman in origin, and was it result of pervasion of all those influences and normatively shaped in the period from the IV-VI centuries? A typological analysis of sample models was also conducted to understand the transformation of design methods, from squinches through a sail vault to a dome on pendentives. Examples of the use of pendentives before the Hagia Sophia from the sixth century indicate that its builders had predecessors, but they undoubtedly deserve the credit for the first use of this solution on such a large scale and so extraordinarily constructive and artistically composed.